Reliability assessment of a coding scheme for the physical risk factors of work-related musculoskeletal disorders - Chen, Yilin; Meyer, John D; Song, Jaechul; McDonald, J Corbett; Cherry, Nicola (Scandinavian Journal of Work, Environment & Health, 2002)
' ' OBJECTIVES ': 'This study assessed the reliability of a novel coding scheme for physical risk factors for musculoskeletal disorders reported to an occupational surveillance scheme. ' ' METHODS ': 'Since 1997 new cases of musculoskeletal disease have been reported as part of a surveillance scheme by over 300 consultant rheumatologists in the United Kingdom; the rheumatologists also gave a short description of the tasks and activities they considered to be causal. With the use of a summary of the activities described, a coding scheme was developed comprising 16 categories of task codes and another 16 categories of movement codes. Four reviewers coded the work activities independently for 576 cases. The fourth rater coded the cases twice. With the use of a single summary kappa statistic and the matrix of kappa coefficients, both interrater reliability and intrarater reliability were assessed. ' ' RESULTS ': 'The overall interrater agreement on the task codes was good (kappa = 0.73), with the best agreement for keyboard work (kappa = 0.96) and the worst for assembly work (kappa = 0.40, kappa = 0.37). The interrater agreement on movement codes was also good (kappa = 0.79), with the best agreement for kneeling (kappa = 0.94) and the worst for materials handling (kappa = 0.10). The intrarater agreement was somewhat better than the interrater agreement with both codes. ' ' CONCLUSIONS ': 'The results suggest that the coding scheme was, on the whole, reliable for classifying the physical risk factors reported as causal.
Keywords: epidemiology; exposure assessment; kappa; occupational musculoskeletal disorder; physical risk factor; reliability assessment; surveillance; work-related musculoskeletal disorder